Dynamics of Handstand Balance - Wyatt, H; Vicinanza, D; Newell, K; Irwin, G; Williams, G (NMU Commons, 2020)
The purpose of this study was to identify parameters that are associated with more successful motor control during handstand performance. For two groups of gymnasts, ‘less skilled’, who were able to hold handstands for 4 to 6s, and ‘more skilled’, who held handstands in excess of 10s, centre of mass (CoM) and centre of pressure (CoP) motion during the initial 3s of the handstand stability phase were analysed, as well as the 6 to 9s stabilised period for the more skilled gymnasts (balance phase). Time-space, time-frequency, CoM-CoP coherence, Hurst Exponent and CoM-CoP causality were investigated in anterior-posterior (AP) and medio-lateral (ML) directions. Characteristics of CoM and CoP for more and less skilled gymnasts were found to be directionally dependent (AP and ML). Nonlinear and frequency domain measures distinguished skill levels to a greater extent than time-space domain measures. The study findings shed light on the subtleties and complexities of the mechanics and dynamics that define CoM and CoP relations with increased skill level, that add to both basic and applied understanding.
Keywords: Nonlinear dynamics; Motor control; Inverted posture